I think you made a typo on the equation, shouldn't it be like this:
z^2-8z=9
If so, I will still help you with the problem, you need to subtract 9 from both sides:
z^2-8z-9=0
You need to factor it:
(z-9)(z+1)=0
z=9 or -1
I hope this helps and it was the answer that you were looking for.
2006-12-29 15:12:18
·
answer #1
·
answered by Anonymous
·
5⤊
0⤋
First: set the equation to equal "0" > subtract 9 from both sides:
z^2 - 8x - 9 = 9 - 9
z^2 - 8x - 9 = 0
Second: factor the equation:
(z - 9)(z + 1) = 0
third: take both sets to equal "0" and solve for "z" >>>
z - 9 = 0
z - 9 + 9= 0 + 9
z = 9
z + 1 = 0
z + 1 - 1 = 0 - 1
z = -1
2006-12-29 16:26:44
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
3⤊
0⤋
z= 9 and/or -1
2007-01-02 10:32:30
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
I think you mean:
z^2 - 8z = 9
If so, this can be solved by factorisation(splitting the middle term):
z^2 - 8z = 9
z^2 - 8z - 9 = 0
z^2 + z - 9z - 9 = 0
z(z + 1) - 9(z + 1) = 0
(z - 9)(z + 1) = 0
Either z - 9 = 0
or z + 1 = 0
If z - 9 = 0
z = 9
If z + 1 = 0
z = -1
z has two possible values.
z = 9, -1
2006-12-29 15:37:07
·
answer #4
·
answered by Akilesh - Internet Undertaker 7
·
4⤊
0⤋
z^2-8x+8x=9+8x
z^2=9+8x
z= the square root of 9+8x
2006-12-29 15:13:26
·
answer #5
·
answered by RoxieC 5
·
1⤊
1⤋
z= +or - the square root of 8x+9
2006-12-29 15:10:41
·
answer #6
·
answered by David G 2
·
1⤊
1⤋
z^2-8x=9
z^2=9+8x
z=square root (9+8x)
2006-12-29 15:07:59
·
answer #7
·
answered by angel 2
·
1⤊
1⤋
i am taking it as a typo
the sum as z^2-8z=9
(z-9)(z+1)=0
z=9 or -1
2006-12-29 15:09:37
·
answer #8
·
answered by raj 7
·
3⤊
0⤋
z² - 8x = 9
z² - 8x + 8x = 9 + 8x
z² = 9 + 8x
z = â9 + 8x
-- - - - -s-
2006-12-30 00:46:05
·
answer #9
·
answered by SAMUEL D 7
·
0⤊
0⤋
+/- sqrt(8x+9) = z
2006-12-29 15:08:33
·
answer #10
·
answered by Dashes 6
·
1⤊
1⤋